Rapid Progression of Primary Sclerosing Cholangitis Complicated with Ulcerative Colitis - Piotr Pardak; Ewa Walczak; Rafał S. Filip (Case Reports in Gastrointestinal Medicine)
Primary sclerosing cholangitis is a cholestatic condition with unknown etiology and long-standing, progressive course, leading to cirrhosis and requiring orthotropic liver transplant. In approximately 80%, primary sclerosing cholangitis is accompanied by inflammatory bowel disease, and in most cases the recognition of bowel disease precedes the diagnosis of primary sclerosing cholangitis. We describe a case of 22-year-old male diagnosed simultaneously with primary sclerosing cholangitis and ulcerative colitis, with a medical history suggesting uncommon prior development of the liver disease. Five months after the initial diagnosis, we observed advanced lesions of bile tree due to progression of primary sclerosing cholangitis, which led to the unusually fast necessity for the orthotopic liver transplant.